Mixing enhancement in jet flow using the air tab technique - Wan, Chao (2012)
It is well known that the triangular tab is an effective device to enhance jet’s mixing. However, due to its protrusion nature, its blockage will induce thrust loss for the jet engine exhausts. This loss varies from 4.1% to 23.7% when the blockage area due to the tabs at the nozzle exit increases from 1.1% to 14.1% (Zaman (1999)). In the present investigation, a technique by injecting a small amount of air at certain angle of attack (AOA) into the primary jet, namely the “air tab”, will be introduced. One of the advantages of this technique is that it will not cause thrust loss as the “solid triangular tab”. The objective of this research is to examine the details of this air tab technique in jet’s mixing experimentally and computationally. The solid tab used for comparison in the present project is the “delta” tab, which has been shown to have the best mixing enhancement effect for the jet flow. Two configurations of the air tab have been considered for comparison with the solid tab, namely the 90 air tab and the 45 air tab defined by the angle between the air injection and the primary jet. The primary jet is firstly operated at subsonic regime (Me=0.8). The jet’s mixing enhancement effect caused by the air tab can achieve the best when the injection velocity is set at M=1.0. The primary jet is subsequently changed to be at supersonic regime (Me=1.3), but the injection velocity for the air tab is maintained at M=1.0. The centerline velocity decay, the variation of the axial velocity contours, the streamwise vorticity contours and the mass flux variation at successive downstream stations have been evaluated and discussed. Flow visualization has also been conducted via Schlieren technique. The experimental results reveal that the injection from the air tab is able to penetrate into the plume of the primary jet so as to shorten the jet’s potential core length and to enlarge the jet’s mixing region with the surrounding air as the behavior of the solid tab. A pair of inwards counter-rotating streamwise vortex is produced when either the solid tab or the air tab is used. And the 90 air tab case shows the best mixing enhancement effect among the three tabbed cases (solid tab case, 90 air tab case and 45 air tab case). At the same time, numerical simulations of the jet’s flow field by using Fluent have been performed.